Polynomial remainder-Nightmare

Let f ( x ) f(x) be polynomial having integer coefficient and degree 99 99 .If f ( 2 999 ) = 13 811986 f({ 2 }^{ 999 })={ 13 }^{ 811986 } then find f ( 4 3987 ) f\left( { 4 }^{ 3987 } \right) Mod 7 7


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jubayer Nirjhor
Nov 21, 2014

Let the polynomial be f ( x ) = k = 0 99 a k x k f(x)=\sum_{k=0}^{99} a_k x^k so that f ( 2 999 ) = k = 0 99 a k 2 999 k = 1 3 811986 k = 0 99 a k 1 ( m o d 7 ) f\left(2^{999}\right)=\sum_{k=0}^{99} a_k 2^{999k}=13^{811986}\implies \sum_{k=0}^{99} a_k\equiv 1\pmod 7 because 2 999 = 8 333 1 ( m o d 7 ) 2^{999}=8^{333}\equiv 1\pmod 7 . Also 4 3987 = 8 2658 1 ( m o d 7 ) 4^{3987}=8^{2658}\equiv 1\pmod 7 . So f ( 4 3987 ) = k = 0 99 a k 4 3987 k k = 0 99 a k 1 ( m o d 7 ) f\left(4^{3987}\right)=\sum_{k=0}^{99} a_k 4^{3987k}\equiv \sum_{k=0}^{99} a_k\equiv \fbox{1}\pmod 7 and note that the degree doesn't matter.

f(4^3987)mod7=f(8^2658)mod7=f((7+1)^2658)mod7=f(1)mod7=f((7+1)^333)mod7=f(8^333)mod7=f(2^999)mod7=13^811986mod7=(2*7-1)^811986mod7=(-1)^811986=1

Iliya Hristov - 1 year, 3 months ago
Joel Tan
Nov 20, 2014

We use the well known fact that if a , b , n a, b, n are integers, n a b n|a-b then n f ( a ) f ( b ) n|f (a)-f (b) .

Note that 4 3987 = ( 4 3 ) 1329 4^{3987}=(4^{3})^{1329} . Since 7 4 3 1 , 7 4 3987 1. 7|4^{3}-1, 7|4^{3987}-1. Also, 7 2 3 1 7 2 999 1 7|2^{3}-1 \implies 7|2^{999}-1 . Thus both have the same remainder when divided by 7, and 1 3 811986 , f ( 4 3987 ) 13^{811986}, f(4^{3987}) have the same remainder too. But 1 3 811986 13^{811986} is congruent to ( 1 ) 811986 = 1 (-1)^{811986}=1 mod 7 so the answer is 1.

Joel Tan Yes that property makes things very easier. I created this problem using that fact.But can you prove it?

shivamani patil - 6 years, 6 months ago

Log in to reply

Every such polynomial can be made using a sum of terms of the form a x n ax^{n} , a a is an integer and n n is a nonnegative integer.

Now we know that for integers c, d, not equal, c-d| c n d n = ( c d ) ( d n 1 + c d n 2 + c 2 d n 2 + . . . + c n 1 c^{n}-d^{n}=(c-d)(d^{n-1}+cd^{n-2}+c^{2} d^{n-2}+...+c^{n-1} .

For n = 0 , 1 , 2 , . . . , D n=0, 1, 2, ..., D where D D is the degree of the polynomial, we can get D+1 of these conditions. Adding them up goves the result.

Joel Tan - 6 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...